MENINGKATKAN KECERDASAN EMOSI SISWA MELALUI KONSELING RATIONAL EMOTIF BEHAVIOR THERAPY DI KELAS XI SMA NEGERI 76 JAKARTA - Supadi 1 Supadi; Evitha Soraya; Dimas Kurnia Robby (Improvement: Jurnal Ilmiah untuk Peningkatan Mutu Manajemen Pendidikan, 2019)
The purpose of this research is to improve student emotion intelligence through Rational Emotif Behavior Therapy Counseling in XI SMA Negeri 76 Jakarta. The research subject is 30 grade XI SMA Negeri 76 Jakarta Year lesson 2018/2019 which has low emotional intelligence. The research methods used are research action Group guidance. Data collection techniques in research are obtained from instruments that are in the form of observation sheets and polls.The results of the study were obtained the average value of emotional intelligence of students before being given REBT counseling treatment of 106.87 or a 53.43% percentage with low category, which has increased after being given REBT counselling treatment At cycle I of 150.73 or percentage of 75.37% with moderate category and increased back in cycle II with obtained average value of 167.93 or percentage 83.97% with medium category. This means that there is an increase in emotional intelligence between before being given an action of 57.14%.